2023
DOI: 10.47836/ifrj.30.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of aflatoxin B1 by Bacillus subtilis YGT1 isolated from yoghurt

Abstract: Aflatoxin contamination of food products is recognised as a major food safety concern throughout the world because of its carcinogenic, mutagenic, and immunosuppressive effects on human health. Of the various types of aflatoxins, aflatoxin B1 (AFB1) is the ubiquitous and most threatening foodborne mycotoxin to humans. A wide range of detoxification methods is used to reduce the toxic effects of AFB1. In the present work, the ability of probiotics isolated from yoghurt (produced by bacterial fermentation of mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…Ali et al [60] reported that P. fluorescens strain SZ1 isolated from soil degraded 100% of AFG1 and 99% of aflatoxin B1, B2, and G2. Al-Mamari et al [19] found that live cells of B. subtilis YGT1 obtained from yogurt degraded 83.8% of AFB1 after 48 h of incubation at 30 • C. El-Nezami et al [71] showed that even heat-and acid-treated dead cells of L. rhamnosus GG could bind AFB1. The peptidoglycan in the cell wall of L. rhamnosus GG has been reported as crucial for binding AFB1 [72].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Ali et al [60] reported that P. fluorescens strain SZ1 isolated from soil degraded 100% of AFG1 and 99% of aflatoxin B1, B2, and G2. Al-Mamari et al [19] found that live cells of B. subtilis YGT1 obtained from yogurt degraded 83.8% of AFB1 after 48 h of incubation at 30 • C. El-Nezami et al [71] showed that even heat-and acid-treated dead cells of L. rhamnosus GG could bind AFB1. The peptidoglycan in the cell wall of L. rhamnosus GG has been reported as crucial for binding AFB1 [72].…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al [73] showed that B. shackletonii L7 significantly reduced AFB1 levels (92.1%), with the culture supernatant degrading more AFB1 than live cells or cell extracts. Al-Mamari et al [19] reported that the culture supernatant of B. subtilis YGT1 degraded 81.3% of AFB1 in culture medium after 48 h of incubation at 30 • C. The furofuran and lactone rings are the critical sites for the toxic effects of aflatoxins. Modifications to these ring structures typically lead to the loss of the toxic effects of aflatoxins [74,75].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations